Organizational change in the light of discourse: a teaching case about a community of people with and without learning disabilities - Santos, Leonardo Blanco dos; Domenico, Silvia Marcia Russi De (Revista de Administração da UFSM, 2017)
This article presents a teaching case focused on the discussion of organizational change, from the perspective of the interpretive paradigm and of the studies of organizational discourse. It describes a process of change within a non-profit organization, where people with and without learning disabilities, the latter called assistants, live in community. The introduction of new government guidelines changed the system of financing of such activity, giving more autonomy to people with learning difficulties and failing to provide activities that were central to the organization’s system of meanings. With the “heart” of the community threatened, assistants express the challenges to experience organizational change, reporting that they are dancing in blood. The case aims to contribute to the discussion of organizational change processes in postgraduate and possibly undergraduate courses, through an unusual perspective, which states the change not only as deliberate, but mainly as something built in participants’ interactions. It also can be used for supporting the discussion between agents and recipients of change in organizations.